An Epitome of Chatbot: A Review Paper - Gupta, Jeetu Kumar; Agarwal, Sohit (International Journal of Computer Sciences and Engineering, 2019)
Chatbot is a technology which is used to do the interactions between the human and the machine, these chatbots can be used in various fields and have various purpose to do the task, where a human can lag behind due to various reasons. Some of the most recent and advance chatbots are in a voice like IBM Watson, Amazon Alexa, Google Assistance, Microsoft's Cortana, Apple Siri, wherein text question and answering we have Google Allo, Mitsuku and many more examples lay down. These all chatbots makes life easier to answer the question for different application in no mean of time. As they were being made with different tools and technology like Natural Language Processing (NLP). The technology of machine learning is growing so rapidly that the implementation of chatbots in the organization, and doing the research can improve the efficiency of it and can perform outstandingly in a different sector. The most demanding sector of chatbot is in the business sector where the customer service plays an important role, as they can do the continuous work, and handles the client by 24/7 support. Chatbot virtual assistance gives genuine feedback support to client, where artificial intelligence and machine learning do the backend work done in processing and giving appropriate answer or output to the user.